PERANCANGAN JARINGAN FIBER TO THE HOME (FTTH) MENGGUNAKAN APLIKASI GOOGLE EARTH PRO - Muhamad Irsal MI; Yuliarman Saragih (Aisyah Journal Of Informatics and Electrical Engineering (A.J.I.E.E), 2023)
ABSTRACT Currently the public's need for internet network access for voice, data and video services continues to increase, to run these services requires very high bandwidth and internet speed. Fiber To The Home (FTTH) is a telecommunications service architecture that utilizes optical network transmission media that supports transmission at bandwidth and internet speeds of up to 100 Mbps. Therefore, it is necessary to develop the FFTH network for areas that do not have internet network access such as the Royal Residence Karawang housing, the development of the FFTH network requires a good design in order to determine the number of devices needed and minimize the use of costs. To design the FTTH Network, the Google Earth Pro application is used to determine the area of ​​the Polygon, the coordinates of the Optical Distribution Point, Poles and Optical Distribution Cabinet. In designing, determining the number of devices and the coordinates of the devices to be installed. Keywords: FTTH; Google Earth Pro; Telecommunication ABSTRAK Saat ini kebutuhan masyarakat akan akses jaringan internet untuk layanan suara, data dan video terus meningkat, untuk menjalankan layanan tersebut membutuhkan bandwidth dan kecepatan internet yang sangat tinggi. Fiber To The Home (FTTH) adalah arsitektur layanan telekomunikasi yang memanfaatkan media transmisi jaringan optik yang mendukung transmisi pada bandwidth dan kecapatan internet mencapai 100 Mbps. Oleh karena itu perlu dilakukan pengembangan jaringan FFTH untuk daerah yang belum memiliki akses jaringan internet seperti perumahan Royal Residence Karawang, pengembangan jaringan FFTH memerlukan desain yang baik agar dapat menentukan jumlah perangkat yang dibutuhkan dan meminimalkan penggunaan biaya. Untuk merancang Jaringan FTTH, digunakan aplikasi Google Earth Pro untuk menentukan luas Polygon, koordinat Optical Distribution Point, Tiang dan Optical Distribution Cabinet. Dalam melakukan perancangan dilakukan penentuan jumlah perangkat dan koordinat perangkat yang akan dipasang. Kata Kunci: FTTH; Google Earth Pro; Telekomunikasi